A coupled mechano-biochemical model for bone adaptation - Klika, Václav; Pérez, Maria Angelés; García-Aznar, José Manuel; Maršík, František; Doblaré, Manuel (Journal of mathematical biology, 2014)
Bone remodelling is a fundamental biological process that controls bone microrepair, adaptation to environmental loads and calcium regulation among other important processes. It is not surprising that bone remodelling has been subject of intensive both experimental and theoretical research. In particular, many mathematical models have been developed in the last decades focusing in particular aspects of this complicated phenomenon where mechanics, biochemistry and cell processes strongly interact. In this paper, we present a new model that combines most of these essential aspects in bone remodelling with especial focus on the effect of the mechanical environment into the biochemical control of bone adaptation mainly associated to the well known RANKL-RANK-OPG pathway. The predicted results show a good correspondence with experimental and clinical findings. For example, our results indicate that trabecular bone is more severely affected both in disuse and disease than cortical bone what has been observed in osteoporotic bones. In future, the methodology proposed would help to new therapeutic strategies following the evolution of bone tissue distribution in osteoporotic patients.
Keywords: RANK Ligand; Osteoprotegerin; Computer Simulation; Adaptation, Physiological; Osteoporosis; Biomechanical Phenomena; fyziologická adaptace; protein RANK; Models, Biological; osteoporóza; Bone Remodeling; ligand RANK; osteoprotegerin; biomechanika; lidé; biologické modely; Humans; remodelace kosti; počítačová simulace; Receptor Activator of Nuclear Factor-kappa B